The Interactions of Nintedanib and Oral Anticoagulants—Molecular Mechanisms and Clinical Implications - Grześk, Grzegorz (Int J Mol Sci, 2020)
Nintedanib is a synthetic orally active tyrosine kinase inhibitor, whose main action is to inhibit the receptors of the platelet-derived growth factor, fibroblast growth factor and vascular endothelial growth factor families. The drug also affects other kinases, including Src, Flt-3, LCK, LYN. Nintedanib is used in the treatment of idiopathic pulmonary fibrosis, chronic fibrosing interstitial lung diseases and lung cancer. The mechanism of action suggests that nintedanib should be considered one of the potential agents for inhibiting and revising the fibrosis process related to COVID-19 infections. Due to the known induction of coagulation pathways during COVID-19 infections, possible interaction between nintedanib and anticoagulant seems to be an extremely important issue. In theory, nintedanib could increase the bleeding risk, thrombosis and lead to thrombocytopenia. The data from clinical trials on the concomitant use of nintedanib and antithrombotic agents is very limited as this patient group was within the standard exclusion criteria. Nintedanib is an important therapeutic option, despite its interaction with anticoagulants. If anticoagulant therapy is necessary, the more effective and safer option is the concomitant administration of DOACs and nintedanib, especially when drug-monitored therapy will be used in patients at high risk of bleeding complications.